Metalogênese do depósito aurífero de Gómez Plata, Cordilheira Central, Colômbia - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
In Colombia, gold mining represents one of the most important sources for the country's economy. The characterization of these deposits is still scarce and represents a challenge in advancing geological and exploratory knowledge. The Colombian Andes have a geodynamic history resulting from the generation of calc-alkaline magmatism on the Pacific margin, which has occurred since the Jurassic period, with accretion of terrains, development of Barrovian, thermal, and high-pressure metamorphism, as well as installation of shear zones and fluid migration. In such a scenario, important gold deposits were generated. Some of the most important deposits are hosted in rocks found in the metallogenic district of Antioquia, such as the Antioqueño Batholith. This body is in the northern portion of the Central Andes, west of the Otú-Palestina (Pericos) fault system, being the only Cretaceous intrusive body recognized in the Central Andes. The Antioqueño Batholith is composed of 5 main intrusive satellite bodies, the Altavista, San Diego, La Culebra, La Unión and the Ovejas Batholith. Such plutons were formed by at least four magmatic pulses, the first three pre-collisional during the Upper Cretaceous dated by U-Pb in zircon at (95-87 Ma, 89-82 Ma, and 81-72 Ma), and the last post-collisional during the Paleocene (~63-58 Ma). The latter pulse is correlatable with other plutons located to the south of the Central Andes such as the Hatillo, Manizales, El Bosque, Norcásia, Sonsón, and to the north, the Santa Marta Batholith and the Parashi stock, on the Caribbean margin. In general, the Antioqueño Batholith is composed of rocks ranging from granitic to granodioritic composition, except for the San Diego stock, which is a gabro. These bodies are intruded by late-magmatic hydrothermal dikes and veins, which are mainly responsible for mineralization in this gold district. In the Gomez Plata region, approximately 200 km from Medellin, the Mocorongo gold deposit is located, consisting of granodiorite intruded by quartz veins and gangue minerals, mainly iron sulfides (pyrite), copper (chalcopyrite), lead (galena), zinc (sphalerite), iron oxides (magnetite and hematite) and gold as subordinate minerals. These veins would have been formed in several pulses since at least three generations of quartz are observed and are controlled by a main shear system with attitudes varying in the range of 250°-70° to 110°-290° and dips between 57°-84°, a structure that maintains a similar orientation to the fault system that controls the Nús River. The deformation associated with this structure is of the protocataclastic type, which is mainly recorded as planar sliding and fracturing in quartz, showing that the shear zone was reactivated after the formation of the veins. These strain mechanisms are indicative that the veins were formed at shallow levels of the upper crust (around 4 to 6 km depth). This shear structure was interpreted as subordinate and conjugate to the regional Otú-Pericos-Palestina shear system. The granodiorite hosting the veins that make up the deposit exhibits evidence of potassic, sericitic, and propylitic alteration, which in the proximity of the mineral veins was obliterated by restricted halos of hydrothermal alteration of sericitic type closer, and chloritic type further away. Considering that chlorite and epidote in the Mocorongo deposit are spatially related to hydrothermal halo zones, and that according to petrographic characteristics, part of the chlorites in the deposit crystallized during the main phase of this process from biotite and amphibole in the host rock. Based on thermobarometry, temperatures between 293.44°C and 329.89°C were calculated for the hydrothermal alteration zone. Aqueous fluid inclusions with homogenization temperatures and salinities in the modal range of 158 to 300°C (mean of 220 ± 32°C; standard deviation of 1σ; n = 93), with higher frequency of maximum peaks between 226 and 253°C and equivalent to NaCl of 2 to 15% (mass%), respectively, and aqueo-carbonic fluid inclusions with clathrate dissolution temperatures ranging from 7.3°C to 7.7°C and homogenization temperatures between 185.8°C to 241.8°C were observed. This suggests that the carbonic phase may be related to the same confinement conditions as the aqueous phase. When plotted on a P-T graph, an isochore with a temperature of 300°C and a pressure of 2.4 Kbar is observed, corresponding to approximately 24 km depth. This pressure may be related to the variations in directed pressure that the rock was conditioned to during the evolution of the hydrothermal fluid. These physicochemical characteristics suggest that post-magmatic fluids, when channeled into regional fractures, experienced temperature decrease, fluid-rock interaction (boiling), and mixing of meteoric fluids caused by initial fracturing and fluid migration. These strong factors were key contributors to the precipitation of gold in supersaturated fluids.
Keywords: Metalogenia; Mineralogia - Classificação; Minerais - Exploração; CIENCIAS EXATAS E DA TERRA: GEOCIENCIAS: GEOLOGIA: METALOGENIA; CIENCIAS EXATAS E DA TERRA: GEOCIENCIAS: GEOLOGIA: PROSPECCAO MINERAL; Metalogênese; Veios de Quartzo; Depósito aurífero polimetálico; Fluidos hidrotermais tardemagmáticos